1966
DOI: 10.1111/j.2153-3490.1966.tb00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport and fallout of stratospheric radioactive debris

Abstract: The average stratospheric residence half-time of particulate radioactive debris, as represented by strontium-90 and manganese-54, was approximately 10 months during the two years following the last atmospheric tests of high yield nuclear weapons. During this interval, the carbon-14 which was produced artificially by nuclear weapons tests showed a stratospheric residence half-time which increamed with time, but averaged about 18 months. It is suggested that the stratospheric residence half-time of particulate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 5 publications
2
32
0
Order By: Relevance
“…The early (774 AD) rise in the Siberian and Altai Δ 14 C data is difficult to reconcile with 14 C results from the 1960s, when high-yield Soviet atmospheric nuclear tests in Novaya Zemlya (~74°N) in September-November 1961 and again in the latter half of 1962 produced very high burdens of excess 14 C in the NH stratosphere (Feely et al 1966). After each major injection, measurements of atmospheric 14 CO 2 in air samples from NH ground stations (Nydal and Lovseth 1983;Levin et al 1985) showed a sharp rise beginning in the early spring of the following year and continuing through the entire NH growing season.…”
Section: M12 Peak Analysismentioning
confidence: 99%
“…The early (774 AD) rise in the Siberian and Altai Δ 14 C data is difficult to reconcile with 14 C results from the 1960s, when high-yield Soviet atmospheric nuclear tests in Novaya Zemlya (~74°N) in September-November 1961 and again in the latter half of 1962 produced very high burdens of excess 14 C in the NH stratosphere (Feely et al 1966). After each major injection, measurements of atmospheric 14 CO 2 in air samples from NH ground stations (Nydal and Lovseth 1983;Levin et al 1985) showed a sharp rise beginning in the early spring of the following year and continuing through the entire NH growing season.…”
Section: M12 Peak Analysismentioning
confidence: 99%
“…In the present context, some central results were obtained by analysis of observations made by a combination of WU-2 and RB57F highflying aircraft (up to about 21 km) augmented by a few balloon profiles to greater altitudes. Among these was the result that the radioactivity that was in gaseous form at 20 km, 14 C in carbon dioxide, had a stratospheric residence time of 16 months, while the many radionuclides that were attached to the stratospheric aerosol had a significantly shorter lifetime of 10 months (Feely et al 1966). The difference was attributed to gravitational settling by the aerosol, allowing the more effective dispersive motions at lower stratospheric altitudes to separate the gaseous and particulate radionuclides and yield a lower residence time for the latter.…”
Section: Meteorological Dynamicsmentioning
confidence: 98%
“…The collected radionuclide data were nonetheless very useful for investigating atmospheric processes 19 . Results show that the transfer of radioactive debris from the stratosphere to the troposphere takes place mainly at the tropopause breaks, with a maximum in spring and a minimum in autumn 13,16,20 .…”
mentioning
confidence: 99%
“…Radioactive particles with radius below 0.02 mm were typically found above 27 km, and particles of larger radius were found between the tropopause and 21 km. Mean residence times of the order of 1-4 years were reported for radioactive particle aerosols in the stratosphere 2,13,15,16,20 . These estimations were based on the rates of change of the stratospheric burden over short timescales (2-4 years), and numerous important factors/parameters were not taken into account.…”
mentioning
confidence: 99%
See 1 more Smart Citation